TEKNIK PEMERIKSAAN RADIOGRAFI OS CLAVICULA PADA KASUS EVALUASI POST ORIF DI INSTALASI RADIOLOGI RSUD WONOSARI - Dyah Ayu Puspitaningtyas; Novita Ambarwati (LPPM Universitas Awal Bros, 2023)
In order to assess the most recent condition of the fracture after 10 months of pen installation, the right clavicle examination approach used in the post-orif evaluation case at the Radiology Installation of the Wonosari Hospital was the Anteriorposterior (AP) projection. This type of study, which was conducted at the Wonosari Hospital's radiology department, is a descriptive study using a case study methodology. collecting patient information via requests for photos, medical examinations, and direct observations. Because the radiographic data are thought to be able to provide information to make a diagnosis, the right clavicle is only examined with a post-orif evaluation case at the Radiology Installation of Wonosari Hospital, using just the Anterior-Posterior (AP) projection without forming an angle.